The Impact of Probiotics in Respiratory Diseases - Rafee H. Askandar; Nasim Ebrahimi (Polytechnic Journal)
Probiotics are viable microorganisms that, if adequately administered, confer great benefits to the host for the prevention or treatment of a wide range of human diseases, including recurrent respiratory tract infection (RRTI), cystic fibrosis, allergies, and chronic obstructive pulmonary disease (COPD). One of the current problems is that the overuse of antibiotics during respiratory tract infection has led to increased resistance to them, which has been demonstrated in numerous examinations that specific lactic acid bacteria (LAB), one of the key probiotics, against bacterial and viral infections of the respiratory and gastrointestinal tract, have a protective effect. On the other hand, changes in the gastrointestinal and respiratory microbiomes, especially lactobacilli and bifidobacteria, lead to an increase in allergies and asthma and a balance in the microbiome may improve symptoms. Probiotics are able to increase the number and activity of leukocytes, neutrophils, and NK cells. They can also increase IL-10 expression and decrease the expression of inflammatory cytokines such as TNF-α, IL-1β, and IL-8. In addition, they maintain high levels of IgA and produce bacteriocin and ruterin that have antimicrobial activity. Without identifying the specific properties of the probiotic strains and identifying the precise mechanism of their action, probiotic treatment would only be a large hypothesis because the therapeutic and clinical outcomes are different. On the other hand, metagenomics have provided information on how the microbiome interacts with host physiology, leading to new therapeutic targets.